Síntese e caracterização de nanocompósitos constituídos por nanoargila e hidrogel para uso agrícola - Ferreira Junior, Carlos Roberto [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The main objective of controlled release systems is to maintain the concentration of certain solute within efficiency level by desired period from a single dose. In the agrochemical case, such technology helps to reduce impacts in the environment. The use of hydrogels as controlled release carrier emerged as a prospective means for exhibit some properties such as biodegradability, biocompatibility and no toxicity. Hydrogel with dispersed nanoclay comprise a new class of nanocomposites that combine the elasticity and permeability of hydrogels with high nanoclay capability to absorb different substances. In this dissertation, nanostructured hydrogels obtained from methacrylic acid (MAA) and varied Cloisite-Na + nanoclay content were synthesized and characterized. The hydrophilic characteristic of the hydrogels was investigated by degree of swelling (Q) using pure water and in saline solutions as swelling media. Fourier transform infrared spectroscopy (FTIR) identified the characteristic bands of the poly (methacrylic acid) (PMAA), nanoclay and a possible interaction between them. The dispersion of the nanoclay platelets in the polymeric matrix was confirmed by X-ray diffraction (XRD). The scanning electron microscopy (SEM) identified a homogeneous morphology, with visibly uniform pores. The energy dispersive X-ray spectroscopy (EDX) showed elements coming of the nanoclay in the nanocomposite, confirming the interaction between both. Thermal properties, performed by thermogravimetry (TG) and derivative thermogravimetry (DTG) analyzes and differential scanning calorimetry (DSC), showed a better thermal performance of the nanocomposites when compared to pure hydrogel. Finally, preliminary tests of controlled release were done and indicated that the nanocomposites present great potential to be applied in agriculture, especially as carrier vehicle in the controlled release of fertilizers

O principal objetivo de sistemas de liberação controlada é manter a concentração de um determinado soluto dentro dos níveis de eficiência por um período desejado com uma única dose. No caso dos agrotóxicos, tal tecnologia auxilia a reduzir impactos ao meio ambiente. O uso dos hidrogéis como veículos de liberação controlada surgiu como um meio promitente por apresentar algumas propriedades tais como: biodegradabilidade, biocompatibilidade e não toxidade. Hidrogéis com nanoargila dispersa compõem uma nova classe de nanocompósitos que combinam a elasticidade e a permeabilidade dos hidrogéis com a alta capacidade das argilas de absorverem diferentes substâncias. Nesta dissertação foram sintetizados e caracterizados hidrogéis nanoestruturados obtidos a partir de ácido metacrílico (MAA) e composições variadas de nanoargila Cloisita Na + . A caracterização hidrofílica dos hidrogéis foi investigada por meio de estudos de grau de intumescimento (Q) usando água pura e soluções salinas como meio de intumescimento. Espectros de absorção na região do infravermelho (FTIR) identificou bandas características tanto do poli(ácido metacrílico) (PMAA) quanto da nanoargila e uma possível interação entre eles. A dispersão das plaquetas de nanoargila na matriz polimérica foi avaliada por difração de raios- X (DRX). A microscopia eletrônica de varredura (MEV) identificou uma morfologia homogênea, com poros visivelmente uniformes. A espectroscopia de energia dispersiva de raios-X (EDX), apresentou elementos da nanoargila nos nanocompósitos, confirmando assim uma interação entre ambos. Propriedades térmicas, feitas por análise termogravimétrica (TG), análise termogravimétrica diferencial (DTG) e calorimetria exploratória diferencial (DSC), apontaram uma melhor estabilidade térmica dos nanocompósitos em comparação ao hidrogel puro. E por fim, testes preliminares de...
Keywords: Produtos químicos agrícolas; Adubos e fertilizantes; Nanotecnologia; Agricultural chemicals